High-Q Fano Resonance in Terahertz Frequency Based on an Asymmetric Metamaterial Resonator - Qin Xie; Guang-Xi Dong; Ben-Xin Wang; Wei-Qing Huang (Nanoscale Research Letters, 2018)
Abstract We propose a planar metamaterial formed by four-strip metallic resonators, which can achieve high-Q Fano resonance in terahertz regime. This terahertz planar metamaterial supports a sharp Fano resonance at 0.81 THz with 25% transmission. The resonance bandwidth of the dip is 0.014 THz with the Q-factor of 58. The interference between the bright mode and dark mode leads to the Fano line shape. This sharp Fano profile is explained by the electromagnetic theory of Fano resonance. Moreover, multiple Fano resonances can be realized by adding more strips into the original structure. As an example, two Fano dips with Q-factors of 61 and 65 can be achieved via a five-strip structure.